2018
DOI: 10.1159/000487033
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Oxymatrine on Vascular Endothelial Cells from High-Glucose-Induced Cytotoxicity by Inhibiting the Expression of A2B Receptor

Abstract: Background/Aims: Diabetes mellitus (DM) has become an increasingly epidemic metabolic disease. Vascular endothelial cells play a key role in developing the cardiovascular complications of DM. The A 2B receptor is expressed in vascular endothelial cells, and may help regulate the function of endothelial cells. The aim of this study was to investigate the protective effects of oxymatrine (OMT) on human umbilical vein endothelial cells (HUVECs) from high glucoseinduced cytotoxicity. Methods: Homology modeling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…High glucose (HG) treatment in HUVECs can induce robust oxidative injury, responsible for following cell death and apoptosis [ 8 , 28 31 ]. Contrarily, antioxidant agents or genetic strategies suppressing oxidative injury can protect HUVECs from HG [ 8 , 28 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High glucose (HG) treatment in HUVECs can induce robust oxidative injury, responsible for following cell death and apoptosis [ 8 , 28 31 ]. Contrarily, antioxidant agents or genetic strategies suppressing oxidative injury can protect HUVECs from HG [ 8 , 28 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…High glucose (HG) treatment in HUVECs can induce robust oxidative injury, responsible for following cell death and apoptosis [ 8 , 28 31 ]. Contrarily, antioxidant agents or genetic strategies suppressing oxidative injury can protect HUVECs from HG [ 8 , 28 , 31 ]. We here also found that HG induced potent oxidative stress in HUVECs, leading to superoxide accumulation ( Figure 2A ), GSH reduction (a GSH/GSSG ratio decrease, Figure 2B ) and significant mitochondrial depolarization (green JC-1 monomers accumulation, Figure 2C ), which were largely attenuated by pretreatment of BARD (50 nM, 1h) ( Figure 2A – 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that glucose is essential for the growth of S. aureus. However, high glucose usually induces endothelial and renal cytotoxicity in diabetic patients (Gao et al, 2015;Yi et al, 2018;Liu et al, 2020). S. aureus is the most frequent pathogen isolated from diabetic foot ulcers, but the properties of this bacterium under high glucose conditions remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that oxymatrine is helpful for the treatment of diabetes. In umbilical vein endothelial cells, oxymatrine alleviates high glucose-induced endothelial toxicity by inhibiting ROS production [ 17 , 18 ]. Oxymatrine can reduce the levels of advanced glycation end products, ROS, and inflammatory cytokines in the kidney of diabetic rats [ 19 ].…”
Section: Introductionmentioning
confidence: 99%